Chambers students' dictionary (Chambers Harrap, 1998)
The book contains over 20.000 words and phrases and 23.000 examples of current English, supported by the British National Corpus; over 1.000 usage notes help avoid common errors, and give opposites; the appendices offer grammar, prepositions, conjunctions, comparatives and superlatives, singular and plural, spelling rules, question tags and punctuations